TSP1–CD47 signaling is upregulated in clinical pulmonary hypertension and contributes to pulmonary arterial vasculopathy and dysfunction. Issue 1 (13th October 2016) - Rogers, Natasha M.; Sharifi-Sanjani, Maryam; Yao, Mingyi; Ghimire, Kedar; Bienes-Martinez, Raquel; Mutchler, Stephanie M.; Knupp, Heather E.; Baust, Jeffrey; Novelli, Enrico M.; Ross, Mark; St. Croix, Claudette; Kutten, Johannes C.; et al.
Abstract : Aims: Thrombospondin-1 (TSP1) is a ligand for CD47 and TSP1 −/− mice are protected from pulmonary hypertension (PH). We hypothesized the TSP1–CD47 axis is upregulated in human PH and promotes pulmonary arterial vasculopathy. Methods and results: We analyzed the molecular signature and functional response of lung tissue and distal pulmonary arteries (PAs) from individuals with ( n  = 23) and without ( n  = 16) PH. Compared with controls, lungs and distal PAs from PH patients showed induction of TSP1–CD47 and endothelin-1/endothelin A receptor (ET-1/ETA) protein and mRNA. In control PAs, treatment with exogenous TSP1 inhibited vasodilation and potentiated vasoconstriction to ET-1. Treatment of diseased PAs from PH patients with a CD47 blocking antibody improved sensitivity to vasodilators. Hypoxic wild type (WT) mice developed PH and displayed upregulation of pulmonary TSP1, CD47, and ET-1/ETA concurrent with down regulation of the transcription factor cell homolog of the v-myc oncogene (cMyc). In contrast, PH was attenuated in hypoxic CD47 −/− mice while pulmonary TSP1 and ET-1/ETA were unchanged and cMyc was overexpressed. In CD47 −/− pulmonary endothelial cells cMyc was increased and ET-1 decreased. In CD47 +/+  cells, forced induction of cMyc suppressed ET-1 transcript, whereas suppression of cMyc increased ET-1 signaling. Furthermore, disrupting TSP1–CD47 signaling in pulmonary smooth muscle cells abrogated ET-1-stimulated hypertrophy. Finally, a CD47 antibody given 2 weeks after monocrotaline challenge in rats upregulated pulmonary cMyc and improved aberrations in PH-associated cardiopulmonary parameters. Conclusions: In pre-clinical models of PH CD47 targets cMyc to increase ET-1 signaling. In clinical PH TSP1–CD47 is upregulated, and in both, contributes to pulmonary arterial vasculopathy and dysfunction.